Household Food Security under Social Forestry: Evidence from a Forest Farmer Group in the Drylands of East Nusa Tenggara, Indonesia - Fransiskus Xaverius Dako; Frenly Marvi Selanno; Yudhistira A.N.R. Ora; Sukriati Andesti Lamanda; Kletus Florianus Sera Gare; Adrin; Blasius Paga; Nusrah Rusadi (Journal of Sylva Indonesiana, 2026)
Forest farmer households in tropical dryland areas represent a vulnerable group whose livelihoods depend heavily on forest resources and rain-fed agriculture, making their food security critical for rural resilience and sustainable development. This study analyzes the food security of forest farmer households who are members of the Fetomnasi Forest Farmers Group in Sillu Village, Fatuleu District, Kupang Regency, East Nusa Tenggara. The research examines the relationship between socioeconomic characteristics, the utilization of non-timber forest products, agroforestry practices, and household food security levels. Data were collected from 24 households through structured interviews and analyzed using descriptive statistics, the Household Food Security Index, and Pearson's correlation test. The results indicate an average food security index score of 0.65, classified as adequate food security. Variations in food security status among households are influenced by income, education, access to information, and the capacity to utilize non-timber forest products. The Fetomnasi Forest Farmers Group plays a strategic role in strengthening household food security through the coordination of agricultural and forestry activities, technical training, facilitation of government assistance, and the development of social capital such as trust and cooperation among members. However, institutional performance remains constrained by limited capital, infrastructure, and management capacity. Strengthening institutional governance, improving access to financial resources, and promoting agroforestry diversification are essential to enhance food security resilience and ensure the sustainability of forest-based livelihoods in tropical drylands. Futere research should examine longitudinal changes in household food security and evaluate the long-term effectiveness of institutional interventions in dryland social forestry systems.